DIET DENSITY IN REARING AND REPRODUCTIVE PHASES INFLUENCES CARCASS COMPOSITION, PREGNANCY RATE AND LITTER PERFORMANCE OF PRIMIPAROUS RABBIT DOES - Teixeira, P. S. S. [UNESP]; Moura, A. S. A. M. T. [UNESP]; Wechsler, F. S. [UNESP]; Fernandes, S. [UNESP]; Mattaraia, V. G. M. (Univ Politecnica Valencia, 2017)
The objective was to evaluate the effect of the interaction of diet density in the rearing phasexdiet density in the reproductive phase on carcass composition, pregnancy rate, and litter performance of primiparous rabbit does. The experiment followed a 2x2x2 factorial (2 seasons, 2 diet densities in the rearing phase and 2 diet densities in reproductive phase, that is, from mating to weaning of the first litter). The reference diet (RD) contained 184 g/kg of crude protein (CP), 165 g/kg of acid detergent fibre (ADF) and 10.5 MJ/kg of digestible energy (DE). The low-density diet (LD) had 147 g/kg of CP, 24 g/kg of ADF and 8.4 MJ/kg of DE. The treatments were applied from 70 d of age until weaning of the first litter at 35 d of age. Ninety-six females from the Botucatu Genetic Group (24 females/experimental group) were mated at 142 d of age. On day 12 of gestation, 23 does were slaughtered to evaluate weights of carcass, organs and dissectible fat, and embryo implantation rate. No effects of diet density in the rearing or in the reproductive phases were detected on feed intake of does during the reproductive phase. Does fed LD during the rearing phase showed lower body weight at mating (3574 47 vs. 3866 43 g, P=0.0001) and during most of the reproductive phase, but they lost less weight in the peripartum. Perirenal fat was lighter in these does (72.8 +/- 10.0 vs. 102.1 +/- 9.6 g, P=0.048) and they showed a lower pregnancy rate (76.1 vs. 91.7%, P=0.045). The does fed RD in the reproductive phase were heavier during this phase (4055 +/- 40 g vs. 3887 +/- 41 g, P=0.0044). The does fed LD in rearing phase and RD in the reproductive phase showed larger litters at weaning, due to decreased kit mortality, than those fed RD in both phases (6.16 +/- 0.47 vs. 3.93 +/- 0.71, P=0.0361). Litters were lighter at weaning when LD was fed in the reproductive phase (3582 +/- 201 vs. 4733 +/- 187, P<0.0001). Feeding a low density diet during the rearing phase and a reference diet during the reproductive phase is the best alternative to improve reproductive performance at the first parity.
Keywords: embryo implantation rate; litter size; perirenal fat; pregnancy rate; rabbit